2014
DOI: 10.1093/jpepsy/jsu082
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Weight Control: An Intervention Targeting Parent Communication and Modeling Compared With Minimal Parental Involvement

Abstract: Contrary to hypotheses, targeting parent-adolescent communication and parental modeling did not lead to better outcomes in adolescent weight control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 43 publications
1
40
1
Order By: Relevance
“…In 1 recent study, adolescents were randomly assigned to an enhanced treatment condition that included standard behavioral weight control combined with targeted parent-adolescent communication and parental modeling of healthy behaviors or a standard behavioral intervention with minimal parental involvement. 31 Contrary to expectation, the results revealed a trend for adolescents randomized to the condition with minimal parent involvement to demonstrate greater decrease in BMI than those who received the enhanced condition. One potential explanation for this finding is that parental modeling of healthy eating and activity behaviors, considered to be a key factor in supporting weight loss in children, is less salient for adolescents.…”
Section: Lifestyle Interventions For Pediatric Weight Controlcontrasting
confidence: 73%
“…In 1 recent study, adolescents were randomly assigned to an enhanced treatment condition that included standard behavioral weight control combined with targeted parent-adolescent communication and parental modeling of healthy behaviors or a standard behavioral intervention with minimal parental involvement. 31 Contrary to expectation, the results revealed a trend for adolescents randomized to the condition with minimal parent involvement to demonstrate greater decrease in BMI than those who received the enhanced condition. One potential explanation for this finding is that parental modeling of healthy eating and activity behaviors, considered to be a key factor in supporting weight loss in children, is less salient for adolescents.…”
Section: Lifestyle Interventions For Pediatric Weight Controlcontrasting
confidence: 73%
“…where effect size was greatest partway through the program at 3 months (6%), reduced at 6 months (4%) and remained stable at 12 months (4%) . Seven programs, ranging in length from 6 weeks to 4 months, reported BMI as an outcome measure and had smaller effect sizes which ranged from 1% to 7% . Two of these programs reported BMI after a period of follow‐up, with the direction of the effect increasing (from 3% at 6 weeks to 4% at 10 weeks ) for one program and decreasing (from 5 to 6% at 4 months to 3–5% at 12 months and 0–2% at 24 months) for the other ).…”
Section: Resultsmentioning
confidence: 99%
“…Study, program and participant characteristics are reported in Table . Half of the programs were from the United States (US; n = 11) with the remainder from Europe ( n = 7) , Australia ( n = 2) and the United Kingdom (UK; n = 1) . The programs were evaluated as controlled trials ( n = 15), both randomized ( n = 10) and non‐randomized ( n = 5) , and as pre–post case series ( n = 6) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the CBT-HL protocol included specific content on Body Image and Coping with Food Cravings (Jelalian et al, 2015). A nutritionist was available to meet with the teen individually up to four times.…”
Section: Methodsmentioning
confidence: 99%